Improving ergonomic conditions and productivity: a case study in a PVD coating production area - Brito, Marlene (2016)
Introduction: Due to demographic variation, fewer young workers are available and the overall number of workers will decrease. The length of absenteeism, especially due to musculoskeletal disorders (MSDs), increases with higher age (Müglich et al., 2015). According to Neumann and Dul (2010), if effectively applied in the design of operation systems, Human Factors can improve system performance while reducing health hazards for employees. The aim of this work is to evaluate “How productivity is affected after the implementation of ergonomics improvements?” The case study takes place in a PVD coating production area, where workers’ complaints due to shoulder pains were rising considerably. These complaints come mainly from the processes of loading and unloading pieces from the suspension, before and after the product entering the PVD machine, respectively. This is a repetitive job and involves two awkward postures: flexion of the arms above 60º (from now on “arms up”) about 30% of the time and the difficulty to move manually a full suspension of 6kg, on average, from the machine carpet to a table every 3 minutes and vice-versa depending if it is an unloading or a loading process.